1992
DOI: 10.1073/pnas.89.15.6866
|View full text |Cite
|
Sign up to set email alerts
|

Mutations induced by methylene blue plus light in single-stranded M13mp2.

Abstract: Reactive oxygen species are generated by a variety of cellular processes. These endogenously generated, reactive intermediates produce a multiplicity of DNA alterations and mutations and have been implicated in the pathogenesis of several human diseases. We report here that treatment of single-stranded M13mp2 bacteriophage DNA with methylene blue and white light generates increased levels of 8-hydroxydeoxyguanosine and that mutagenesis is both highly specific and dependent on the SOS response. Lesions produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Loeb and co-workers have clearly shown that while this tandem double mutation, a hallmark of damage to DNA by UV irradiation, is not produced by DNA polymerases or viral reverse transcriptases or by exposure to chemical carcinogens, it can be caused by oxidative damage to DNA Tkeshelashvili et al, 1993). G:C to C:G and G:C to T:A transversions, which were also found to be present at relatively high frequencies in the lung cancers of our non-smoker cohort, are also known to be induced by reactive oxygen species in certain circumstances (Moriya et al, 1991;McBride, 1992). The present findings suggest that oxygen radical species, which can be generated by various mechanisms, including normal cellular processes (Fridovich, 1983), might have a role in the development of lung cancers.…”
Section: Discussionmentioning
confidence: 57%
“…Loeb and co-workers have clearly shown that while this tandem double mutation, a hallmark of damage to DNA by UV irradiation, is not produced by DNA polymerases or viral reverse transcriptases or by exposure to chemical carcinogens, it can be caused by oxidative damage to DNA Tkeshelashvili et al, 1993). G:C to C:G and G:C to T:A transversions, which were also found to be present at relatively high frequencies in the lung cancers of our non-smoker cohort, are also known to be induced by reactive oxygen species in certain circumstances (Moriya et al, 1991;McBride, 1992). The present findings suggest that oxygen radical species, which can be generated by various mechanisms, including normal cellular processes (Fridovich, 1983), might have a role in the development of lung cancers.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, however, tandem double CC -+ TT mutations have been detected in forward mutation assays when using either Cu ions (12) or human neutrophils as a source of reactive oxygen species (13). The goal of this study was to determine whether oxygen free radicals were responsible for inducing this mutation and (15,27). Because of the rarity of CC -* TT mutations, we have elected to use SOS-induced cells to increase the sensitivity with which they can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen radicals cause a large number of modifications to cytosine residues, and single C -* T transitions are among the most common mutations produced by most (12,15) but not all (27) reactive oxygen species. Chemical modifications produced by reactive oxygen at cytosine residues include addition to the 5,6 double bond of the pyrimidine ring, formation of glycols, hydantoins, deamination products, and species with rearrangements of the pyrimidine ring (7,8).…”
Section: T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t 5'-c-c-amentioning
confidence: 99%
“…All proteins, lipids, carbohydrates and nucleic acids are harmed by these radicals [7]. Moreover, it has been that various mutations occurred in DNA following the treatment with demonstrated methylene blue and light, as well as heredical diseases occurred in metabolic pathways [14].…”
Section: Introductionmentioning
confidence: 99%